Exchange bias properties in Sr2LnRuO6 (Ln = Dy, Ho and Er). (6th December 2017) - Mohanty, Prachi; Marik, Sourav; Singh, Deepak; Singh, Ravi P
Abstract: Herein, we report the exchange bias effect in S r 2 L n R u O 6 (Ln = Dy, Ho and Er) compounds. These ruthenium-based double perovskite compounds exhibited the exchange bias effect below their AFM ordering temperatures when they cooled in the presence of a magnetic field. Detailed magnetization measurements indicate that the exchange bias properties may associate with the Dzyaloshinskii–Moria (D–M) interactions originated due to the low crystallographic symmetry in these system types.